Using the hybrid DAS-SR method for damage localization in composite plates. (1st September 2020) - Nokhbatolfoghahai, A.; Navazi, H.M; Groves, R.M.
Abstract: In this paper, the hybrid Delay-And-Sum (DAS) with Sparse Reconstruction (SR) method was further developed for damage location in composite plates. In composite materials, anisotropy leads to some challenges in using conventional damage location methods, which are developed for isotropic materials. In the hybrid DAS-SR method, the DAS and SR methods were combined as a complement of each other. To investigate the DAS-SR method for composite structures, the group velocity of the travelling wave for different directions was first measured experimentally via PZTs. The DAS and SR formulations were then modified to be compatible with the direction-dependent group velocities. The results show that this modification increases the accuracy of the DAS and SR methods for damage location in a composite plate. However, using group-velocity instead of phase-velocity in the standard SR method, causes some model mismatch and errors in the damage localization and this problem was solved by using the modified hybrid DAS-SR method. The experimental results demonstrated that the performance of the modified hybrid method for detection and location of barely visible impact damages as well as for multi-location artificial damages is better than that of the DAS and SR methods when separately used.